2019
DOI: 10.1128/aac.01595-19
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities of β-Lactam–β-Lactamase Inhibitor Antimicrobial Agents against Cystic Fibrosis Respiratory Pathogens

Abstract: We tested the in vitro activities of ceftazidime-avibactam, ceftolozane-tazobactam, meropenem-vaborbactam, piperacillin-tazobactam, and 11 other antimicrobial agents against 420 Burkholderia, Achromobacter, Stenotrophomonas, and Pandoraea strains, 89% of which were cultured from respiratory specimens from persons with cystic fibrosis. Among the β-lactam–β-lactamase inhibitor agents, meropenem-vaborbactam had the greatest activity against Burkholderia and Achromobacter, including multidrug-resistant and extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 13 publications
(12 reference statements)
6
21
0
Order By: Relevance
“…Notably, although AVI did not restore the activity of CAZ against the two MDR S. maltophilia isolates, it did restore the activity of ATM against the two MDR S. maltophilia strains with significant MIC reductions of 32- and 8-fold respectively. The poor activity of CAZ-AVI against MDR S. maltophilia isolates was in accordance with a previous study by Lindsay J. Caverly et al [ 17 ], who demonstrated that the activity of CAZ-AVI was poor against most MDR/XDR S. maltophilia strains. Recently, the efficacy of CAZ-AVI (2.5 g i.v.…”
Section: Discussionsupporting
confidence: 91%
“…Notably, although AVI did not restore the activity of CAZ against the two MDR S. maltophilia isolates, it did restore the activity of ATM against the two MDR S. maltophilia strains with significant MIC reductions of 32- and 8-fold respectively. The poor activity of CAZ-AVI against MDR S. maltophilia isolates was in accordance with a previous study by Lindsay J. Caverly et al [ 17 ], who demonstrated that the activity of CAZ-AVI was poor against most MDR/XDR S. maltophilia strains. Recently, the efficacy of CAZ-AVI (2.5 g i.v.…”
Section: Discussionsupporting
confidence: 91%
“…However, acquired resistance to these are increasingly being reported (64). The proportion of ceftazidime-susceptible isolates was 71% in a U.S. collection (susceptibility breakpoint, Յ8 g/ml; CLSI other non-Enterobacterales; MIC 50/90 , 8/32 g/ml) (65). In another collection from Europe, trimethoprimsulfamethoxazole MIC 50/90 was 0.5/8 g/ml (susceptibility breakpoint Յ 2 g/ml, CLSI other non-Enterobacterales), and it was one of the two most active agents against 59 Achromobacter isolates, the other being imipenem (MIC 50/90 , 2/8 g/ml) (66).…”
Section: Antibiotic Susceptibilitymentioning
confidence: 99%
“…In vitro data indicate similar resistance profiles to ceftazidime and ceftazidime-avibactam (MIC 50/90 of 32/> 32 and 16/> 32 mg/L, respectively), meropenem and meropenem-vaborbactam (MIC 50/90 of> 32/ > 32 and > 32/> 32 mg/L, respectively), and imipenem and imipenem-relebactam (MIC 50/90 of > 64/> 64 and > 64/> 64 mg/L, respectively). 12,13 Ceftolozane-tazobactam offers no additional benefit to ceftazidime-resistant isolates.…”
Section: Mechanisms Of Resistancementioning
confidence: 99%